Developing Problem Based Learning Module Containing Multiple Levels of Representation of Ksp Material to Improve Students' Problem Solving Ability - Sulistiyanti, Irma; Haryani, Sri; Cahyono, Edy (International Journal of Active Learning, 2021)
Research is based on the mastery of problem solving abilities is still low and the teaching materials used in learning lack training and develop students' problem-solving abilities. This study aims to develop a module based on problem-based learning and contains multiple levels of representation in the solubility material and its solubility product which is feasible and to determine the improvement of students' good problem solving abilities. The research method used is research and development (Research and Development) and the learning modules are arranged according to PBL. Data were collected through expert validation sheets, tests and questionnaires. The results of the validation of the material experts, linguists and media experts respectively showed very good results with an assessment percentage of 93.98%, 86.03% and 88.39%. The results of module trials by students through questionnaires received very good feasibility assessments with a percentage of 78.89% and the results of module trials by teachers got very good assessments with a percentage of 96.83%. The results of the application of problem-based learning modules obtained data in the form of pretest-posttest values which were tested using the n-gain test. The n-gain test results obtained a value of 0.56 in the medium category. The results of this test indicate that there has been an increase in the problem-solving abilities of students after using the module. Based on the results obtained, it can be concluded that the PBL-based chemistry learning module on the solubility material and the solubility product developed is very effective and suitable for use in chemistry learning processes in schools.